Hedgehog Pathway and Programmed Cell Death Protein-1 Inhibitors for Advanced Basal Cell Carcinoma - Babette J.A. Verkouteren; An K.L. Reyners; Maureen J.B. Aarts; Klara Mosterd (Karger Publishers, 2024)
Introduction: Basal cell carcinoma (BCC) is treated with local surgery or noninvasive treatment modalities. If a BCC remains untreated, it can develop into a locally advanced BCC or a metastatic BCC. Case Presentation: Here we report in detail the management of three complex advanced BCC (aBCC) after treatment failure with vismodegib. On all tumors, next generation DNA sequencing in the Center for Personalized Cancer Treatment-02 (CPCT-02) study was performed; subsequently, patients were included in the Drug Rediscovery Protocol (DRUP) trial, in which treatment was started with commercially available targeted anticancer drugs based on the molecular tumor profile. All patients showed partial response or stable disease following treatment with second line PD-1 inhibitors with an average duration of response of 12.3 months. Discussion/Conclusion: Immunotherapy can be a treatment option for aBCC resistant to hedgehog pathway inhibitor treatment. However, despite the high tumor mutational burden of aBCCs, immunotherapy does not always lead to a long response. Rechallenge or combining treatment of hedgehog inhibitors and PD-1 inhibitors by parallel or alternating cycles may be a strategy to lengthen the treatment response.